Ecosystem respiration and foliar morphology of a primary tropical rain forest: the effects of canopy structure and environmental gradients - Cavaleri, Molly A., author; Binkley, Daniel, advisor; Ryan, Michael, advisor (Colorado State University. Libraries, 2007)
Wood and foliage are major components of ecosystem respiration, but estimates of large-scale rates for tropical rain forests are uncertain because of poor sampling in the upper canopy and across landscapes. Carbon balance models often rely on leaf mass per area (LMA) because it correlates with many plant physiological parameters. Researchers have long assumed variation in LMA to be a response to light (sun/shade leaf dichotomy), but LMA also reflects increases in leaf density that result from decreasing water potential with height. We used a portable scaffolding tower to measure plant respiration, LMA, and light from ground level to the canopy top across 55 sites in a primary tropical rain forest in Costa Rica. The first objective of this study was to extrapolate woody CO2 efflux to the forest by characterizing its variation with canopy structure and landscape gradients. The second objective was to extrapolate foliar and total respiration to the forest by investigating the variation in foliar respiration with foliar parameters, canopy structure, and landscape gradients. The third objective was to determine whether LMA varied primarily because of light or water potential. Wood and foliage respiration rates increased with height and showed differences between plant functional groups. Wood respiration per unit ground area was 1.3 μmo1 CO2 M-2 s-1 and foliar respiration was 3.5 μmol CO2 m-2 s-1, representing 14% and 37% of total ecosystem respiration, respectively. Total ecosystem respiration (9.38 ± 1.43 μmol CO2 m-2 s-1) was 33% greater than eddy flux nighttime net ecosystem exchange for the same forest, suggesting that eddy flux studies reporting a large sink for tropical rain forests may be in error. We found LMA to be better related to height than light environment, supporting the hypothesis that the LMA gradient within forest canopies is primarily driven by a linear decrease in turgor pressure with height, caused by an increase in hydraulic resistance with gravity and longer path length. While light does affect LMA slightly, especially in the light-limited understory, the sun/shade leaf model taught in every plant physiology textbook is too simplistic to describe the large variation of LMA with vertical structure.
Keywords: canopy; foliage; rainforests; respiration; tropical; ecology